Heterozygous NOTCH1 deletion associated with variable congenital heart defects. Issue 6 (2nd May 2021) - Roifman, Maian; Chung, Brian Hon Yin; Reid, Diane Myles; Teitelbaum, Ronni; Martin, Nicole; Nield, Lynne E.; Thompson, Megan; Shannon, Patrick; Chitayat, David
Abstract: Pathogenic heterozygous variants in the NOTCH1 gene are known to be associated with both left and right‐sided congenital cardiac anomalies with strikingly incomplete penetrance and variable phenotypic expressivity. De novo NOTCH1 whole gene deletion has been reported rarely in the literature and its association with cardiac defects is less well established. Here, we report four cases of NOTCH1 gene deletion from two families associated with a spectrum of congenital heart defects from bicuspid aortic valve to complex cardiac anomalies. This is the first description of a familial NOTCH1 deletion, showing apparently high penetrance, which may be unique to this mechanism of disease. Immunohistochemical staining of cardiac tissue demonstrated reduced levels of NOTCH1 expression in both the left and right ventricular outflow tracts. These cases suggest that haploinsufficiency caused by NOTCH1 gene deletion is associated with both mild and severe cardiac defects, similar to those caused by pathogenic variants in the gene, but with apparently higher, if not complete, penetrance. Abstract :